Analisis Determinan Keputusan Konsumen Muslim Membeli Green Product - Nanda Naufal Rofiza Haidar; Achmad Firdaus; Mukhamad Najib (Esensi: Jurnal Bisnis dan Manajemen, 2020)
The study aims to determine the effect of Collectivism, Eco-Literacy, Green Advertising, Spirituality and Environmental Concern on the intention to buy environmentally friendly products All Fresh on Indonesian Muslim consumers. The research consisted of three stages namely the study of literature. Then a field study was conducted by distributing questionnaires to 270 respondents. The analysis method used is Structural Equation Modeling (SEM) using AMOS. The results showed that the variables Collectivism, Eco-Literacy, Green Advertising and Spirituality showed a significant and positive effect on Environmental Concern. Furthermore, these variables show a significant and positive relationship to the attitude toward green products (ATGP) of Indonesian Muslim consumers.